The clinical utility of genome‐wide non invasive prenatal screening. (12th May 2017) - Fiorentino, Francesco; Bono, Sara; Pizzuti, Francesca; Duca, Sara; Polverari, Arianna; Faieta, Monica; Baldi, Marina; Diano, Laura; Spinella, Francesca
Abstract: Objective: In this study, we expanded conventional cell‐free fetal DNA (cfDNA)‐based non‐invasive prenatal testing (NIPT) to cover the entire genome. We aimed to compare the performance of the two tests in a large general population of pregnant women, in order to assess the clinical utility of the genome‐wide screening. Method: Genome‐wide cfDNA analysis was offered to 12 114 pregnant women undergoing NIPT for common fetal aneuploidy. Sequencing data were analyzed using an algorithm optimized to identify aneuploidies and subchromosomal aberrations. Results: Genome‐wide screening allowed detection of 12 (7.4%) potentially viable clinically relevant chromosomal abnormalities, which would have remained overlooked if only conventional NIPT had been performed. This resulted in a statistically significant higher sensitivity (100% vs 92.64%, p  < 0.001) than did standard screening. This was achieved without sacrificing the specificity of the test, which resulted similar to that obtained with standard cfDNA testing (99.87% vs 99.77%, p  = 0.064). Conclusion: Genome‐wide cfDNA analysis represents an enhanced screening tool for prenatal detection of chromosomal abnormalities, allowing identification of clinically relevant imbalances that are not detectable by conventional cfDNA testing. The results of this study demonstrate the clinical utility of genome‐wide cfDNA analysis. This level of screening provides a significant higher sensitivity compared to standard screening while maintaining a high specificity, with the potential to improve overall pregnancy management. © 2017 John Wiley & Sons, Ltd. Abstract : WHAT'S ALREADY KNOWN ABOUT THIS TOPIC? Conventional cfDNA‐based NIPT focuses on detection of common aneuploidies, leaving a gap of ~17% of clinically relevant chromosomal abnormalities that would go undetected. Genome‐wide NIPT would greatly expand the range of chromosomal rearrangements detectable, but it could lead to a decrease of the specificity and, consequentially, to an increase in unnecessary invasive testing. WHAT DOES THIS STUDY ADD? This study demonstrates the clinical utility of expanding NIPT to cover the entire genome. Genome‐wide cfDNA analysis provides a significant higher sensitivity compared to standard screening while maintaining a high specificity.